ANALISIS GAYA BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN 2 GUBUGSARI - Aryana, Nerisa; Rofian; Mira Azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study started from students of grade IV SDN 2 Gubugsari who were slow in the learning process such as students having difficulty remembering and not understanding the material presented by the teacher, and students being less active during the Indonesian language learning process. This study was conducted with the aim of describing students' learning styles in the Indonesian language subject of grade IV SDN 2 Gubugsari. This study used a descriptive qualitative approach with 33 subjects of grade IV students. Data collection techniques through observation, questionnaires, interviews, and documentation. The results of the study showed that the learning style of grade IV students of SDN 2 Gubugsari was a combination of visual learning styles, auditory learning styles, and kinesthetic learning styles with different learning style tendencies. The learning style of students in the Indonesian language subject of grade IV SDN 2 Gubugsari was predominantly an auditory learning style.